British Council’s initiatives for the Polish community in the stagnation time of the Cold War (1949-1952) (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
The problem of cultural activity of British Council’s Polish post from its reactivation to further development in the course of two turbulent years of the post-war era, has not been taken upon in literature. The paper aims to present the data on British Council’s initiatives in Warsaw, based on queries made in the National Archives in London. The context is set in the times of communist-entrenching in Poland, focusing on the stagnation time of the Cold War (1949-1952), when all contacts of Western diplomats and officials with the Polish community were being gradually restrained. The communist regime continuously supervised the cultural content proposed by British diplomatic missions, though British Council continued its mission.